Mathematical Model and Advance Control for Activated Sludge Process in Sequencing Batch Reactor - Ibrehem, Ahmmed; Hussain, Mohammed Azlan (ASEAN Journal of Chemical Engineering, 2009)
This paper presents the results of a modeling and simulation study of an activated sludge process in a sequencing batch reactor (SBR), with emphasis on total nitrogen removal. This study focuses on the effect of dissolved oxygen (DO) and effluent chemical oxygen demand (COD). Neural-network based redictive controller (MPC) is implemented to control the system for the DO set point and give better and acceptable results when compared with the conventional PID controller